ChemInform Abstract: A Highly Diastereoselective Oxa‐Pictet‐Spengler Approach to (+)‐Astropaquinone B and (+)‐Astropaquinone C and the Formation of Astropaquinone B Dimer. Issue 20 (20th May 2014) - Fernandes, Rodney A.; Mulay, Sandip V.
Abstract Astropaquinone B (IV) is accompanied by minor amounts of its dimer (not shown).